iPhone for seniors in easy steps - Vandome, Nick (Leamington Spa, Warwickshire, United Kingdom In Easy Steps, 2021)
"iPhone for Seniors in easy steps, 8th edition is now updated to cover all iPhones with iOS 15. It'll show you how to: Make and receive calls and send messages; Use FaceTime to make video calls, and have fun sharing music or video clips on FaceTime calls; Find apps to stay healthy, shop online, plan your vacation, get instant news, and keep on top of everyday tasks; Make secure payments using your iPhone; Customize your iPhone and notifications; Explore the iTunes Music Library; Share music, videos, apps, calendars and photos with children and grandchildren. Written in larger type and using non-technical language, iPhone for Seniors in easy steps, will help you get more out of your iPhone--so you don't have to ask the kids!"--
Your new iPhone -- Starting to use your iPhone -- Head in the iCloud -- Calls and contacts -- Typing and texts -- Camera and photos -- The online world -- Hands on with apps -- Apps for every day -- On the go -- Practical matters.
Includes index.
"Covers all iPhones with iOS 15."
110229
Keywords: iOS (Electronic resource); iPhone (Smartphone); Operating systems (Computers); Computers and older people; Personal computers; Computers and society; Instructional and educational works